Method for preparing high-stability conductive paste from hydrogenated butyronitrile
By pretreating hydrogenated nitrile rubber and preparing conductive paste with high-pressure microjet process, the problems of uneven dispersion and poor heat resistance of conductive paste under high voltage and high magnification conditions are solved, and its performance is significantly improved.
Patent Information
- Application Number
- CN202411705782.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-21
AI Technical Summary
The existing conductive paste has problems such as uneven dispersion, poor heat resistance of dispersants, and easy deactivation under high voltage and high rate charging and discharge conditions, which affects the performance of lithium-ion batteries.
The conductive paste is prepared by pretreating hydrogenated nitrile rubber, reducing molecular weight, and combining with a high-pressure microjet process to improve its viscosity and dispersion.
The heat resistance, dispersion, stability and processing properties of the conductive paste are significantly improved, the viscosity stability is extended, and the resistance is reduced, which proves that the hydrogenated nitrile rubber conductive paste has better dispersion.
Smart Images

Figure CN119661914A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium batteries, and in particular to a hydrogenated nitrile conductive slurry used in manufacturing lithium batteries and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, good safety performance and low cost, and have broad application prospects in the field of new energy: as power batteries, they can be widely used in plug-in hybrid vehicles, electric vehicles, etc.; as digital batteries, they can be widely used in mobile phones, computers, drones, etc. In the continuous development of lithium-ion batteries, the requirements for high-voltage platforms and high-rate charge and discharge of batteries are getting higher and higher, and in the manufacturing process of lithium-ion batteries, the stability and uniformity of the conductive slurry directly affect the safety and chemistry of the finished battery.
[0003] Conductive paste, as an electronic functional material, is widely used in the manufacture of electronic components. It is not only used in lithium-ion batteries, but also widely used in major fields such as inks, capacitors and electric heating. At present, domestic conductive paste is most widely used in the fields of lithium-ion batteries and electric heating.
[0004] Conductive slurry is a uniform paste prepared by mixing and stirring the conductive phase, bonding phase and organic carrier, and three-roll rolling. After screen printing, leveling, drying, sintering and other processes, a conductive film layer with a thickness of several microns to tens of microns is formed on the substrate.
[0005] In the battery field, the conductivity of lithium-ion battery electrode materials can be improved by adding conductive paste. However, the reported conductive paste formulas basically use a large amount of one or more of polyurethane resins, acrylic resins, epoxy resins, etc. as system film-forming substances. Due to the addition of a large amount of resin, the carbon content accounts for a small proportion. Since the resin itself is not conductive, the conductive properties of the conductive paste obtained after adding it are average. In order to meet the high requirements for the conductive properties of the conductive paste, it is necessary to reduce or avoid the addition of film-forming resins in the carbon-based conductive paste as much as possible and increase the carbon content to improve the conductive properties of the conductive paste. At the same time, since the conductive paste contains a conductive phase, a solvent, a bonding phase and a dispersing aid, the selection and matching of each component has a great influence on the formation and overlap of the conductive filler thermal conductive network in the conductive paste.
[0006] As a new macromolecular dispersant in recent years, hydrogenated nitrile (HNBR) is gradually replacing the traditional PVP macromolecular chain dispersant. The high temperature resistance of HNBR can reach 180℃, which is much higher than the 130℃ of PVP-K30. The cold resistance of HNBR is -55~-38℃, and it has excellent mechanical properties and good swelling resistance to technical liquids (including oils containing corrosive additives). Compared with other polymers, it can better meet the requirements of the automotive industry. However, hydrogenated nitrile has high Mooney viscosity and high strength. Its high molecular weight and wide distribution range are not conducive to processing and affect the viscosity of the conductive paste.
[0007] CN117154057A discloses a graphene-modified positive electrode material. The preparation method thereof comprises the following steps: mixing graphene, an organic acid, a binder and a solvent to obtain a graphene conductive slurry; mixing and drying the graphene conductive slurry and a positive electrode material to obtain a graphene-modified positive electrode material. By introducing a binder and an organic acid into the graphene conductive slurry, the coating effect can be improved and the release of lithium inside the material can be reduced. The positive electrode material prepared by the method has good structural integrity, good uniformity of the coating layer, high uniformity of particle size, and effectively improves the performance of the positive electrode material.
[0008] CN117334911A discloses a positive electrode conductive paste. The positive electrode conductive paste comprises carbon nanotubes, a dispersant and a solvent; the oxidative decomposition voltage of the dispersant is greater than 5V. This overcomes the conductive network destruction and electrolyte side reactions caused by the open-ring decomposition of the dispersant polyvinyl pyrrolidone under high voltage due to the unstable five-membered ring structure.
[0009] CN118099428A discloses a high conductivity and low viscosity conductive additive, and the preparation method comprises the following steps: premixing a conductive agent, a dispersant, a viscosity reducer and a solvent, and adding the premixed mixture to a sand mill for grinding, wherein the dispersant is a low molecular weight hydrogenated nitrile rubber; adding the sand mill material to a homogenizer for homogenization, and obtaining a high conductivity and low viscosity conductive additive. The obtained conductive slurry can not only maintain high conductivity, but also keep the viscosity of the slurry at a low level, and the slurry has a significant viscosity stabilizing effect.
[0010] CN118280633A discloses a graphene conductive paste. The raw materials used for the conductive paste include 4.0-15.0% conductive carbon, 0.5-3.0% dispersant, 0.01-1.0% regulator, and 81-95.49% solvent in weight percentage; wherein the conductive carbon includes ≥20% graphene by weight; the dispersant includes hydrogenated nitrile rubber; the solvent is selected from one or two of N-methylpyrrolidone and triethyl phosphate, so as to achieve the effect of obtaining a graphene conductive paste with better viscosity stability.
[0011] At present, conductive pastes have problems such as uneven dispersion, poor heat resistance of dispersants, and easy deactivation, which in turn affect the performance of lithium-ion batteries. Therefore, it is necessary to provide a new conductive paste to prepare lithium-ion batteries with good electrochemical properties. Summary of the invention
[0012] The present invention aims to improve the viscosity and dispersibility of hydrogenated nitrile rubber, specifically to use a special process to treat hydrogenated nitrile, improve the poor viscosity and dispersibility of traditional hydrogenated nitrile, and avoid battery overheating under high-rate working conditions, thereby causing dispersant inactivation.
[0013] In order to achieve the above object, the first aspect of the present invention discloses a method for preparing a high-stability conductive paste by hydrogenating butyronitrile, comprising the following steps:
[0014] (1) pre-treating the hydrogenated nitrile rubber to reduce the molecular weight of the hydrogenated nitrile rubber;
[0015] (2) shearing and crushing the pre-treated hydrogenated nitrile rubber and dissolving it in a solvent to obtain a hydrogenated nitrile rubber dispersion;
[0016] (3) Add the dispersed colloid obtained in step (2) to the conductive material, firstly fully wet the conductive material by premixing and grinding, and then prepare the conductive slurry by high-pressure microfluidization process.
[0017] Preferably, the hydrogenated butyronitrile has a Mooney viscosity of 20-60 ML (1+4) at 100° C. and a saturation of 93% to 99.5%.
[0018] The saturation of hydrogenated nitrile rubber will affect the antioxidant performance of the battery during charging and discharging. If the saturation is low, there will be more double bonds. Excessive double bonds will undergo electrochemical oxidation, thus affecting the battery performance; low Mooney viscosity and low rubber are preferred, with low molecular weight and narrow distribution range. As a dispersant for conductive slurry, it can not only play a good dispersing role, but also maintain good processing performance.
[0019] The pretreatment process in step (1) is one or more of plasticating, mixing, calendering, extrusion, and thin-pass; through the pretreatment, the macromolecular chain of hydrogenated nitrile rubber can be straightened to have better processing performance.
[0020] The plasticizing process conditions are as follows: the film temperature is 30-80°C, the roller distance of the roller machine is 6-10mm, the speed ratio is 1:1.1-1:4, the rollers are plasticized 2-5 times, and then the roller moment is adjusted to 2-5mm to strengthen the shearing effect, and the rollers are plasticized 3-5 times;
[0021] The mixing process conditions are: the mixer temperature is maintained at 100-140° C., the mixing time is 5-10 minutes, and the filling volume of the mixer is maintained at 60-80%;
[0022] The calendering process conditions are as follows: the main roller speed is 5-15 m / min, the adjacent roller speed ratio is maintained at 1:1.1-1:4, the material temperature is 40-80°C, and the roller moment is selected to be 2-8 mm;
[0023] The extrusion process conditions are as follows: first preheat the extrusion equipment, set the barrel temperature to 40-60°C, the die temperature to 65-90°C, and the die temperature to 80-100°C. After reaching the preheating temperature, start the screw feeding, and keep the screw speed at 10-80r / min;
[0024] The thin-pass process conditions are: roller moment 0.2-5mm, temperature controlled at 40-80°C, thin-pass times 3-15 times, roller speed 10r / min-20r / min, and the adjacent roller speed ratio is maintained at 1:1.1-1:4.
[0025] The dissolution conditions in step (2) are: a dissolution temperature of 70-100° C., a stirring speed of 1000-2000 rpm / min, and a time of 6-10 hours; after dissolution, the solid content in the solvent can reach 10%-30%.
[0026] The solvent in step (2) is one or more of n-propanol, isopropanol, acetone, N-methylpyrrolidone, dimethylformamide, dimethylacetamide and xylene.
[0027] The conductive paste in step (3) comprises a conductive material, a dispersant and a solvent, wherein the mass content of the solvent is 88.0-98.8%, the mass content of the dispersant is 0.2-2.0%, and the mass content of the conductive agent is 1-10%;
[0028] The conductive agent is one or a mixture of carbon nanotubes, graphene, carbon black and VGCF.
[0029] In the step (3), the microfluidization process pressure is 100-200 MPa, the number of times is 3-10 times, the flow rate is 0.3L-3L, the discharge temperature is less than 65°C, and the nozzle diameter is 130μm-200μm.
[0030] The second aspect of the present invention discloses a hydrogenated nitrile rubber conductive paste obtained by the preparation method of the present invention.
[0031] The cavitation effect, impact effect and shear effect generated by high-pressure homogenization make the agglomerated materials evenly dispersed. The dispersion of carbon tubes is achieved by flexible collision between internal carbon tubes, which can protect the integrity of carbon tubes to a great extent, thereby improving their conductivity. The high-pressure homogenization process can achieve better dispersion, which is conducive to reducing viscosity and viscosity rebound. It has played a role in promoting the fluidity and solid content of the positive electrode after homogenization.
[0032] The beneficial technical effects of this application are: significantly improving the heat resistance, dispersibility, stability and processing performance of high voltage conductive paste. The hydrogenated nitrile conductive paste also has significant improvements in 6-month viscosity stability and 24-hour viscosity change, and has good processing performance; the lower resistance can also be reflected in the conductivity of the pole piece, proving that the hydrogenated nitrile rubber has better dispersibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 : Comparison chart of viscosity stability of the conductive paste obtained in Example 1 and Comparative Example 1;
[0034] Figure 2 : SEM image of the conductive paste obtained in Example 1;
[0035] Figure 3 : SEM image of the conductive paste obtained in Example 2;
[0036] Figure 4 : SEM image of the conductive paste obtained in Example 3;
[0037] Figure 5 : SEM image of the conductive paste obtained in Example 4;
[0038] Figure 6 : SEM electron microscope image of the electrode piece made of the conductive paste prepared in Example 1;
[0039] Figure 7 : SEM electron microscope image of the pole piece made of the conductive paste prepared in Example 2;
[0040] Figure 8 : SEM electron microscope image of the electrode piece made of the conductive paste prepared in Example 3;
[0041] Fig. 9 : SEM electron microscope image of the electrode piece made of the conductive paste prepared in Example 4;
[0042] Fig.10 : Comparative Example 1 is a SEM electron microscope image of a conductive paste made of common PVP-K30 on the market;
[0043] Fig.11 : SEM electron microscope image of the electrode piece of the conductive paste prepared in Comparative Example 1;
[0044] Fig.12 : SEM image of the conductive paste obtained in Comparative Example 2;
[0045] Fig.13 : SEM image of the conductive paste obtained in Comparative Example 3. DETAILED DESCRIPTION
[0046] Example 1
[0047] The hydrogenated nitrile rubber was thin-passed 10 times under the conditions of a roller distance of 4mm and a speed ratio of 1.1, and then 0.1kg of the hydrogenated nitrile after thin-passing was sheared and crushed into 2cm particles, placed in a stirring kettle, added with 9.5kg NMP, heated to 90°C, and stirred at a speed of 1000rpm for 8h; 0.4kg of carbon nanotubes were added as a conductive agent, and after pre-mixing and grinding to fully infiltrate the powder conductive material, a high-pressure microjet process of 150MPa was used for 6 times to obtain a conductive slurry. The SEM picture is as follows Figure 1 shown.
[0048] Example 2
[0049] The hydrogenated nitrile rubber was thin-passed for 6 times under the conditions of a roller distance of 5mm and a speed ratio of 1.1, and then 0.15kg of the hydrogenated nitrile after thin-passing was sheared and crushed into 2cm particles, placed in a stirring kettle, added with 9.35kg of NMP, heated to 95°C, and stirred at a speed of 1100rpm for 8h; 0.5kg of carbon nanotubes were added as a conductive agent, and after pre-mixing and grinding to fully infiltrate the powder conductive material, a high-pressure microjet process of 180MPa was used for 8 times to obtain a conductive slurry. The SEM picture is as follows Figure 2 shown.
[0050] Example 3
[0051] The hydrogenated nitrile rubber was thin-passed 8 times under the conditions of a roller distance of 4mm and a speed ratio of 1.2, and then 0.05kg of the hydrogenated nitrile after thin-passing was sheared and crushed into 2cm particles, placed in a stirring kettle, added with 9.45kg NMP, heated to 95°C, and stirred at a speed of 1100rpm for 8h; 0.3kg of carbon nanotubes, 0.1kg of graphene and 0.1kg of conductive carbon black were added as conductive agents, and after pre-mixing and grinding to fully infiltrate the powder conductive material, a high-pressure microjet process of 160MPa was used for 8 times to obtain a conductive slurry. The SEM picture is as follows Figure 3 shown.
[0052] Example 4
[0053] The hydrogenated nitrile rubber was thin-passed 8 times under the conditions of a roller distance of 4mm and a speed ratio of 1.1, and then 0.08kg of the hydrogenated nitrile after thin-passing was sheared and crushed into 2cm particles, placed in a stirring kettle, added with 9.45kg NMP, heated to 95°C, and stirred at a speed of 1200rpm for 10h; 0.36kg of carbon nanotubes, 0.06kg of graphene and 0.18kg of conductive carbon black were added as conductive agents, and after pre-mixing and grinding to fully infiltrate the powder conductive material, a high-pressure microjet process of 140MPa was used for 7 times to obtain a conductive slurry. The SEM picture is as follows Figure 4 shown.
[0054] Comparative Example 1:
[0055] 0.1kg PVP-K30 was added to 9.5kg NMP and stirred for 30min. 0.4kg carbon nanotubes were added as a conductive agent. After premixing and grinding to fully wet the powder conductive material, the conductive slurry was prepared by conventional sand milling at a speed of 2300rpm / min for 5h. The SEM image is shown in the figure. Figure 5 shown.
[0056] Comparative Example 2
[0057] 0.1g hydrogenated nitrile rubber was directly sheared and crushed into 2cm particles, placed in a stirring kettle, added with 9.5kg NMP, heated to 90°C, and stirred at a speed of 1000rpm for 23h until the HNBR rubber was completely dissolved; 0.4kg carbon nanotubes were added as a conductive agent, and after premixing and grinding to fully infiltrate the powdered conductive material, a high-pressure microjet process of 150MPa was used for 6 times to obtain a conductive slurry.
[0058] The other parts are the same as those in Example 1, except that the conductive paste is prepared without pretreatment. The SEM image is as follows: Fig.12 Comparative Example 3
[0059] The hydrogenated nitrile rubber was thin-passed for 10 times under the conditions of a roller distance of 4 mm and a speed ratio of 1.1, and then 0.1 kg of the hydrogenated nitrile after thin-passing was sheared and crushed into 2 cm particles, placed in a stirring kettle, added with 9.5 kg of NMP, heated to 90°C, and stirred at a speed of 1000 rpm for 8 hours; 0.4 kg of carbon nanotubes were added as a conductive agent, and after pre-mixing and grinding to fully wet the powder conductive material, a conventional sand milling process was adopted at a speed of 2300 rpm / min for 5 hours to obtain a conductive slurry.
[0060] The other parts are the same as Example 1, except that the high-pressure homogenization microfluidization treatment is not performed, and the conductive slurry is prepared by the traditional sand grinding process. The SEM image is as follows: Fig.13 shown.
[0061] Performance Test:
[0062] Examples of using conductive paste in lithium battery positive electrode
[0063] The conductive paste obtained by Example 1 and Comparative Examples 1, 2, and 3 is directly used for NCM 622 slurry mixing, coating (PET film), and testing body resistivity by means of existing technology. The electrode formula is NCM: CNT: PVDF = 97%: 1%: 2%, solid content 75%, 25% solvent NMP, PVDF is polyvinylidene fluoride, and LCO is battery-grade lithium cobalt oxide. The stability of Example 1 and Comparative Examples 1, 2, and 3 is shown in the following figure:
[0064] Table 1
[0065]
[0066] From the above data, it can be seen that the viscosity stability and electrode resistivity of the conductive paste prepared by using pre-treated hydrogenated nitrile as a dispersant and high-pressure homogenized microfluidization technology are better than those prepared by the traditional PVP-K30 as a dispersant and sanding process. In addition, it can be clearly seen from the SEM image that the diameter of carbon nanotubes is better retained and the dispersion effect is better when hydrogenated nitrile is used as a dispersant and the conductive paste is prepared by high-pressure microfluidization technology.
[0067] It should be noted that the above examples are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention is described in detail with reference to the given examples, those skilled in the art may modify or replace the technical solution of the present invention as needed without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a high-stability conductive paste by hydrogenating butyronitrile, comprising the following steps: (1) pre-treating the hydrogenated nitrile rubber to reduce the molecular weight of the hydrogenated nitrile rubber; (2) shearing and crushing the pre-treated hydrogenated nitrile rubber and dissolving it in a solvent to obtain a hydrogenated nitrile rubber dispersion; (3) Add the dispersed colloid obtained in step (2) to the conductive material, firstly fully wet the conductive material by premixing and grinding, and then prepare the conductive slurry by high-pressure microfluidization process.
2. The method according to claim 1, characterized in that The hydrogenated butyronitrile has a Mooney viscosity of 20-60 ML (1+4) at 100° C. and a saturation of 93% to 99.5%.
3. The method according to claim 1, characterized in that The pretreatment process in step (1) is one or more of plasticating, mixing, calendering, extrusion, and thin-pass; through the pretreatment, the macromolecular chain of hydrogenated nitrile rubber can be straightened to have better processing performance.
4. The method according to claim 3, characterized in that The plasticizing process conditions are as follows: the film temperature is 30-80°C, the roller distance of the roller machine is 6-10mm, the speed ratio is 1:1.1-1:4, the rollers are plasticized 2-5 times, and then the roller moment is adjusted to 2-5mm to strengthen the shearing effect, and the rollers are plasticized 3-5 times; The mixing process conditions are as follows: the mixer temperature is maintained at 100-140° C., the mixing time is 5-10 min, and the filling volume of the mixer is maintained at 60-80%; The calendering process conditions are: main roller speed 5-15m / min, adjacent roller speed ratio maintained at 1:1.1-1:4, material temperature 40-80°C, roller moment 2-8mm; The extrusion process conditions are as follows: first preheat the extrusion equipment, set the barrel temperature to 40-60°C, the die temperature to 65-90°C, and the die temperature to 80-100°C. After reaching the preheating temperature, start the screw feeding, and keep the screw speed at 10-80r / min; The thin-pass process conditions are: roller moment 0.2-5mm, temperature controlled at 40-80°C, thin-pass times 3-15 times, roller speed 10r / min-20r / min, and the adjacent roller speed ratio is maintained at 1:1.1-1:
4.
5. The method according to claim 1, characterized in that The dissolution conditions in step (2) are: a dissolution temperature of 70-100° C., a stirring speed of 1000-2000 rpm / min, and a time of 6-10 hours; after dissolution, the solid content in the solvent can reach 10%-30%.
6. The method according to claim 1, characterized in that The solvent in step (2) is one or more of n-propanol, isopropanol, acetone, N-methylpyrrolidone, dimethylformamide, dimethylacetamide and xylene.
7. The method according to claim 1, characterized in that The conductive paste in step (3) comprises a conductive material, a dispersant and a solvent, wherein the mass content of the solvent is 88.0-98.8%, the mass content of the dispersant is 0.2-2.0%, and the mass content of the conductive agent is 1-10%.
8. The method according to claim 1, characterized in that The conductive agent is one or a mixture of carbon nanotubes, graphene, carbon black and VGCF.
9. The method according to claim 1, characterized in that In the step (3), the microfluidization process pressure is 100-200 MPa, the number of times is 3-10 times, the flow rate is 0.3L-3L, the discharge temperature is less than 65°C, and the nozzle diameter is 130μm-200μm.
10. A conductive paste prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Graphene modified positive electrode material and preparation method and application thereof
CN117154057A
Positive electrode conductive paste, positive electrode paste, positive plate, lithium ion battery and preparation method
CN117334911A
High-conductivity low-viscosity conductive additive as well as preparation method and application thereof
CN118099428A
Graphene conductive paste and preparation method thereof
CN118280633A